(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the resistance of Nile tilapia leather as a function of slaughter body weight classes and leather directions (longitudinal and transverse) in relation to fish body length. The skins were classified into different body weight categories (C1 = 500 to 600 g; C2 = 601 to 700 g and C3 = 701 to 800 g) and frozen for later tanning. After thawing and tanning using chromium salts and retanning with vegetable tannin, the specimens were removed. Followed by the determination of the thickness to carry out the tests of tensile strength and stretching and progressive tearing, using the EMIC dynamometer. The skin area was determined and through linear regression analysis, it was found that there is a correlation between the skin area (Y) and fish weight (X), which can be expressed by the linear equation Y=39,359 + 0, 0269X (r=0.56**). There was an effect of the fish weight class on the force loads applied in the leather strength tests and in the leather transverse direction with higher tensile strength and progressive tear compared to the longitudinal. The chromium oxide content present in the leathers ranged from 3.75 to 3.81%, and 8.16% to 8.47% of extractable substances in dichloromethane and the final pH of the leather ranged from 3.84 to 3.86 between the weight categories. The tanned tilapia hides weighing between 500 and 800 g did not show significant difference in strength, in terms of traction, elongation and progressive tearing. However, when the direction of removal of the specimens was evaluated, the transverse direction (referring to the width of the leather) presented greater resistance in terms of traction and progressive tearing when compared to the longitudinal direction (length of the leather).